Education in Times of the Pandemic COVID 19: Reflections From the Investigative Pedagogical Final Practice - Novoa Romero, Luis Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In this reflective essay, I want to show the situation that I experienced in the last semester of my career, which was the investigative pedagogical final practicum at the Universidad Pedagógica y Tecnológica de Colombia. I started developing this last stage in the “Escuela Normal Superior Santiago de Tunja”. Then, I had to change the institution, and I finished my practice in the “Institución Educativa Libertador Simón Bolívar”. In this process, the COVID 19 pandemic was expanding in almost every country, and the world stopped the normal development of activities, which included the academic institutions. For that reason, I decided to reflect about education around the world and some of the challenges that are always present. Also, I wanted to talk about the new difficulties related to the virus and the ways teaching could implement technological devices and internet connection. Finally, I write some of the implications that I consider important in these difficult times in which education will not stop.